Large deflections of agglomerated carbon nanotubes reinforced sandwich cantilever beam partially embedded on foundation - Bui, Thi Thu Hoai; Tran, Thi Thu Huong; Pham, Vu Nam; Nguyen, Dinh Kien (Comptes Rendus. Mécanique)
The large deflections of a carbon nanotubes (CNTs) reinforced sandwich cantilever beam partially embedded on Pasternak foundation are studied considering the influence of CNTs agglomeration. The sandwich beam is composed of a homogeneous core and composite face layers with effective moduli being estimated by Eshelby–Mori–Tanaka model. The nonlinear equilibrium equation is constructed using a first-order shear deformable nonlinear beam element and solved by the Newton–Raphson based iterative procedure. The result reveals that the effect of slenderness ratio on the large deflections is dependent on the degree of CNT agglomeration, and this effect is more significant when the agglomeration degree is more severe. The effects of the CNT volume fraction, the degree of CNTs agglomeration and the foundation parameters on the large deflections are studied in detail. The influence of the sandwich configuration and the porosities on the behavior of the sandwich beam is also examined and discussed.